Systemic air embolism after computed tomography-guided hook wire localization: two case reports and literature review - Yi, Jung Hoon; Choi, Pil Jo; Bang, Jung Hee; Jeong, Sang Seok; Cho, Joo Hyun (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Computed tomography (CT)-guided hook wire localization is often used to identify small nodules prior to video-assisted thoracoscopic surgery (VATS). Pneumothorax, intrapulmonary hemorrhage, and wire dislodgement are well-known complications associated with the former procedure, but systemic air embolism (SAE) is an extremely rare and potentially fatal complication. We encountered two cases of SAE; one patient showed neurologic symptoms, whereas the other did not. With the patient in the supine position, 100% oxygen was inhaled via a face mask. Subsequently, symptoms were resolved, and we performed planned surgeries on that day. Operative and postoperative courses were uneventful, and both patients were discharged without any sequelae. In this case report, we describe our experience with the two patients and review related literature.